2005
DOI: 10.1159/000084526
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Celiac Disease in Patients with Lactose Intolerance

Abstract: Background/Aims: Acquired lactase deficiency is a common cause of gastrointestinal symptoms but its etiology remains unclear. Celiac disease could lead to lactase deficiency and is much more common than previously suspected. Several studies have highlighted the prevalence of lactose intolerance in celiac disease, but studies assessing the prevalence of celiac disease in lactose intolerance are lacking. We evaluated the prevalence of celiac disease in patients with a positive H2-lactose breath test c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 40 publications
1
35
3
11
Order By: Relevance
“…Serologic screening for coeliac disease in all patients with a positive H2-lactose breath test should be carried out before beginning a milk-exclusion diet. 39 Lactose intolerance in IBD was thought to be a cofactor that predisposed to a clinical attack or it is a consequence or accompanying phenomenon of the disease. Several studies have shown variable prevalence of LI in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic screening for coeliac disease in all patients with a positive H2-lactose breath test should be carried out before beginning a milk-exclusion diet. 39 Lactose intolerance in IBD was thought to be a cofactor that predisposed to a clinical attack or it is a consequence or accompanying phenomenon of the disease. Several studies have shown variable prevalence of LI in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…A possible daily caloric impairment could thus take place. Recently it has been shown that lactase deficiency seems to be the only manifestation of CD [21] .…”
Section: Clinical and Nutritional Featuresmentioning
confidence: 99%
“…Bei Patienten mit Sprue kommt es durch die geschä-digte Dünndarmschleimhaut gehäuft auch zu einer sekundären Lactoseintoleranz [11,12]. Andererseits findet sich offenbar bei Patienten mit Lactoseintoleranz eine erhöhte Prädisposition für die Ausbildung einer Sprue [2].…”
Section: Epidemiologieunclassified
“…Unter Berücksichtigung der Ätiologie lässt sich der Lactasemangel weiter unterteilen, wobei die Klassifikation bei verschiedenen Autoren nicht immer einheitlich ist [2,24]. Übereinstimmend wird die primäre (z.B.…”
Section: äTiologie Und Pathogeneseunclassified
See 1 more Smart Citation